Copper‐Mediated Intramolecular Amidation/C−N‐Coupling Cascade Sequence: Straightforward One‐Pot Synthesis of N‐Aryl γ‐ and δ‐Lactams by Using Amino Acids as Precursors. Issue 41 (3rd November 2022) - Chowdhury, Sushobhan; Chauhan, Gunjan; Kumar, Ajay; Chaturvedi, Bipin; Behera, Chinmaya
Abstract: γ‐And δ‐lactams are important structural motifs present in a wide range of natural products, biologically active molecules, and functional materials. In this work, we disclose an operationally simple, one‐pot, straightforward synthesis of N‐aryl γ‐ and δ‐lactams through a copper‐mediated cascade intramolecular amidation/C−N‐coupling sequence. Starting from the readily available, cheap γ‐/δ‐amino acids and aryl halides, a variety of N‐aryl γ‐ and δ‐lactams have been synthesized in moderate to excellent yields under external ligand or additive‐free aerial conditions. Abstract : In this work, an operationally simple, one‐pot, straightforward synthesis of N‐aryl γ‐ and δ‐lactams has been disclosed. Readily available, cheap γ‐/δ‐amino acids and aryl halides were used as starting materials to synthesize a variety of N‐aryl γ‐ and δ‐lactams by using copper‐mediated cascade intramolecular amidation/C−N‐coupling sequence.